Crispy Burger / Haziq Shahran Sham ... [et al.] - Shahran Sham, Haziq; Dzulhelmy, Muhammad Danish; Farid Zamri, Syamir Rafiq; Sahul Bahari, Adam Asyraaf; Ahmad Dahlan, Arif Danial (2022)
The business we have started is named Crispy Burger. Crispy Burger is a western influenced restaurant where we serve high quality, premium crispy chicken burgers. Our business is based in Johor Bahru. We chose Johor Bahru as the location for our restaurant because the cost of living in Johor Bahru is suitable with our business as our products are priced in the middle class range. Our target market majorly consists of university students and families who like to enjoy burgers as much as we like to make them. The way we promote our business will surely be of help to boost sales and increase our popularity among the locals. Our mission is to become the go-to burger joint for burger lovers in the city. Financially, we aim to achieve a good profit and cement our place in the restaurant business as one of the most well managed businesses in the city.